PENDIDIKAN TATA KRAMA UNTUK ANAK USIA DINI: MANNERS EDUCATION FOR EARLY CHILDHOOD - Fadhilah, Alya Nur (Thufuli, 2021)
Manners education is something that must be given to an early childhood. Early childhood education is  a sensitive age in the beginning of life, this age became the foundation for the further education. Teachers have an obligation to educate children, including about manners. This research is a qualitative research with case study approached. Data were collected by an observation and an interviews. The validity used a triangulation. The results of this research are the teachers didn’t depends the manners education with a video, they uses hands-on practice habits for manners education with basic manners such as saying the words “sorry, please, thank you”, knocking on doors before entering the room and greetings, listening to others when they are talking and not interrupting.